DINAMIKA POPULASI IKAN GABUS (Channa striata) DI RAWA DANAU PANGGANG, KALIMANTAN SELATAN - Dini Sofarini; Mohammad Mahmudi; Asus Maizar S. Hertika; Endang Yuli Herawati (Universitas Lambung Mangkurat, 2018)
The province of South Kalimantan has the largest peat swamp that is named Danau Panggang Swamp with an area of 5,390.7 Ha. This swamp has ecological, economic and potential functions of a large fishery resource. The purposes of this study are to evaluate the exploitation rate of Snake Head Fish (Channa striata) in Danau Panggang Swamp, by population dynamic analysis using FISAT program of Von Bertalanffy method. The results showed that the growth pattern of Snake Head Fish (Channa striata) has the tendency to grow negative allometric with 63.4 cm of long infifer (L¥), growth rate (k) 0.15 per year, theoretical age at the time of the fish is equal to 0 (t0) is -1.48257 years. While the natural mortality rate (M) was 0.43, the mortality rate due to catch (F) of 0.69/year and the total mortality rate (Z) of 1.12/year, and the rate of exploitation value E = 0.62. These results indicated that the exploitation rate of Head Snake Fish (Channa striata) in Danau Panggang swamp has a tendency to overfishing.